Descriptive Study of the Urinary Tract Infections in Patients Admitted in the Cardiology Ward of Afghan Momand Medical Complex - Akmal, Shams; Ikramullah, Ibrahimi; Asif, Agha Said (Journal of Cardiology and Cardiovascular Medicine, 2024)
Urinary Tract Infection (UTI) is very common in our community most specifically in married females with numerous antecedent risk factors. The aim of the study was to find out about the current risk factors and clinical profile of urinary tract infections in patients admitted to the cardiology ward of Afghan Momand Medical Complex for various purposes. It was a cross-sectional descriptive hospital-based study including both male and female patients visiting the Afghan Momand Medical Complex from January 2022 to June 2022. Of all 960 patients, 202 (21%) patients had urinary tract infections with gender distribution as 69 (34.2%) males and 133 (65.8%) females. In fact, 33 (16.3%) patients with urinary tract infections were single while the rest 169 (83.7%) patients were married. In addition, regarding clinical profile, the following clinic was respectively more prevalent: Dysuria in 120 (59.4%) patients, flank pain in 73 (36.1%) patients, urine frequency in 67 (33.1%) patients, urgency in 36 (17.8%) patients, fever in 24 (11.8%) patients, and nausea and vomiting in 19 (9.4%) patients. Moreover, the following risk factors were respectively the most common ones: Diabetes mellitus 86 (42.5%), pregnancy 30 (14.9%), stones 15 (7.4%), 10 (4.9%) devices, 10 (4.9%) prostatic hyperplasia, and 4 (2%) anatomical anomalies. Urinary tract infection is a common disease in the admitted patients in Afghan Momand Medical Complex specifically being more common in females and early 20s of the age. In fact, diabetes, pregnancy, and kidney stones were the leading associated factors with UTI. Moreover, dysuria, bladder emptying irritative symptoms, and abdominal pain were the most prevalent clinical profile of the patients. Special attention should be paid to infectious diseases in cardiac patients since infection itself is a stress and a threat to such patients and authorities should design special measures to prevent UTI in the general population to avoid a sum of burden on the health system.